2020
DOI: 10.1016/j.omtn.2019.11.021
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA UCA1 Functions as a ceRNA to Promote Prostate Cancer Progression via Sponging miR143

Abstract: UCA1 (urothelial carcinoma associated 1) is a long non-coding RNA (lncRNA) that was found overexpressed in various human cancers including prostate cancer (PCa). However, the aspect of UCA1-miRNA-mRNA interaction in PCa remains unclear. In this study, we confirmed the role of UCA1 in PCa and found that UCA1 downregulation inhibited cell proliferation of PCa cells. Then we demonstrated that repressed UCA1 promoted the microRNA-143 (miR-143) expression and miR-143 could bind to the predicted binding site of UCA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 21 publications
0
68
0
Order By: Relevance
“…Understanding the mechanisms underlying the oncogenic activities of PRNCR1 in TScc can elucidate TScc pathogenesis and may aid in developing novel diagnostic and therapeutic methods for this type of cancer. Accumulated evidence has indicated that lncRNAs are capable of modulating gene expression through sponging of miRNAs; the mechanism is known as the ceRNA model (49)(50)(51). In the present study, miR-944 was predicted to have a high probability of binding to PRNCR1.…”
Section: Discussionmentioning
confidence: 52%
“…Understanding the mechanisms underlying the oncogenic activities of PRNCR1 in TScc can elucidate TScc pathogenesis and may aid in developing novel diagnostic and therapeutic methods for this type of cancer. Accumulated evidence has indicated that lncRNAs are capable of modulating gene expression through sponging of miRNAs; the mechanism is known as the ceRNA model (49)(50)(51). In the present study, miR-944 was predicted to have a high probability of binding to PRNCR1.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies have revealed that lncRNAs can act as competing endogenous (ce)RNA for miRNAs in order to modulate human cancer progression ( 28 , 29 ). For example, the lncRNA urothelial cancer associated 1 acts as a ceRNA of miR-143 to promote prostate cancer progression ( 30 ). The lncRNA IGFL2-AS1 sponges miR-802 to regulate cAMP regulated phosphoprotein 19 expression in gastric cancer ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…xenografted tumor growth of LNCaP cells ( Figure S2D) is consistent with previous findings. 18,53 The explanation for the discrepancy may be the different functions of E-cadherin in vitro and in vivo. Cancer cells that expressed E-cadherin display less migratory behavior in vitro, but E-cadherin accelerates tumor establishment and cell proliferation at a secondary site in vivo.…”
Section: F I G U R Ementioning
confidence: 99%